1985
DOI: 10.1073/pnas.82.10.3178
|View full text |Cite
|
Sign up to set email alerts
|

Beta-endorphin-(1-27) is a naturally occurring antagonist to etorphine-induced analgesia.

Abstract: The potent opioid peptide ,-endorphin is found in the brain and pituitary with two related fragments, fi-endorphin-(1-27) and f3-endorphin-(1-26 Recent studies have shown that P-endorphin (p-EP) is found in the pituitaries and the brain of various species together with two related peptides: P-EP-(1-27) and its des-His27 or des-Tyr27 derivative ,-EP-(1-26). Each of these peptides occurs also in an a-N-acetyl form (1-5). Studies of the regional distribution and biosynthetic pathways of the 1-EPrelated peptides i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…It has been repeatedly demonstrated that differential processing mechanisms exist for activation of plurifunctional biosynthetic precursors in various tissues (22)(23)(24)(25)(26)(27)(28). The tissue-specific sets of end products resulting from alternate processing are usually released in a coordinate manner and could exert distinct or coordinated biological activities (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been repeatedly demonstrated that differential processing mechanisms exist for activation of plurifunctional biosynthetic precursors in various tissues (22)(23)(24)(25)(26)(27)(28). The tissue-specific sets of end products resulting from alternate processing are usually released in a coordinate manner and could exert distinct or coordinated biological activities (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the endogenous cannabinoid receptor ligand anandamide is a partial agonist in rat brain (Mackie et al, 1993;Childers et aI., 1994). Moreover, it has been reported that the opioid peptide ß-endorphin 1_27 may act as an agonist (McKnight et al, 1983), an antagonist (Hammonds et al, 1984;Nicholas and Li, 1985;Suh et al, 1987;Bals-Kubik et al, 1988), or a lowefficacy partial agonist at ‚u-and 8-opioid receptors (Hong et al, 1993) in various experimental paradigms. This is unlike ß-endorphin1.31, which has been found to act as a full agonist at ‚u receptors, and a full-or high-efficacy partial agonist at 6-opioid receptors (Law et al, 1983;Selley and Bidlack, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…223). As described above, ␤-LPH is cleaved by PC2 to give ␥-LPH and ␤-endorphin which can be further cleaved by CPE to ␤-endorphin (1-27) and ␤-endorphin (1-26), which have much less analgesic activity (269). These enzymes act in secretory granules within cells, so this implies that the cleavage of ␤-endorphin to the COOH-terminally truncated ␤-endorphin peptides is a mechanism to reduce opioid activity in tissues where other POMC peptides are released for non-opioid functions.…”
Section: The Opiate Activity Of ␤-Endorphinmentioning
confidence: 99%
“…If it is the latter, then there may be processing mechanisms to inactivate ␤-endorphin when melanocortins are activated, and vice versa. Although inactivation by acetylation of ␤-endorphin is not thought to occur in the hypothalamus (258), it may be that processing to ␤-endorphin (1-27) and ␤-endorphin (1-26) is a mechanism that at least reduces its activity (269). As early as the 1920s there were suggestions that the endogenous opioid system was involved in the regulation of food intake and body weight, with morphine causing a decrease in body weight but a "voracious" appetite.…”
Section: Hypothalamic ␤-Endorphin Function and Regulation Of Energy Bmentioning
confidence: 99%